MAQAMAT (TAHAPAN YANG HARUS DITEMPUH DALAM PROSES BERTASAWUF) - Miswar Miswar (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2017)
Abstract:Maqamat is plural form of word of maqam, what Ianguagely mean degree or rank. In English, maqamat referred as with term of stations or of stages. Whereas according to science term of tasawuf, maqamat is to domicile a slave before Allah, obtained through observance, mujahadat and others, practice of spritual and also relation which do not break him with Allah of swt. or technically maqamat also mean maximal effort and activity a sufi to increase the quality of spiritual and dimiciling him ( maqam) before Allah of swt. with certain deeds until the existence of guide to alter at concentration to other certain deed, which is diyaini as higher level deed of its value of him before Allah of swt. Keywords:Maqamat, Station, Process, Riyadoh, Mujahadah.